Identifikasi Cemaran Mikroba pada Kosmetik Sediaan Lip Tint dan Lip Cream dengan Metode Angka Lempeng Total (ALT) - Melia Sari; Leny; Ahmad Faisal Nasution; Ema Erliza (Jurnal Indah Sains dan Klinis, 2025)
Background: Repeated use of these products can lead to microbial contamination, making lip tint and lip cream susceptible to microbial contamination. Objective: To find contamination and identify the types of microbes contained in lip color cosmetics and lip creams. Methods: The methods used for bacterial contamination analysis include the Total Plate Count (TPC) test, bacterial identification on selective agar media, and Gram staining. Results: The Total Plate Count (TPC) results for lip tint samples after 1 month of use were 1.50 x 102 colonies/ml, 2 months 5.00 x 102 colonies/ml, and 3 months 5.50 x 102 colonies/ml. For lip cream samples after 1 month of use, the counts were 1.50 x 102 colonies/ml, 2 months 2.50 x 102 colonies/ml, and 3 months 15.00 x 102 colonies/ml. Pathogenic microbes detected in lip tint samples used for 1-3 months included S. aureus and C. albicans, while lip cream samples used for 1-3 months contained S. aureus, P. aeruginosa, C. albicans, and E. coli. All products that have been sampled for testing are within acceptable limits for Total Plate Count (TPC) according to BPOM Regulation Number 16 of 2024. Conclusion: All tested lip tint and lip cream samples met the required standards